The use of facial nerve fasciculus motor evoked potential (MEP) as intraoperative neurophysiological monitoring modality in a child with a diffuse intrinsic pontine glioma: A case report. (November 2021) - Al-Salihi, Mohammed Maan; Ayyad, Ali; Al-Jebur, Maryam Sabah; Khan, Robert Ahmed; Rahman, Md Moshiur; Rahman, Sabrina
Abstract: Background: Intraoperative neurophysiological monitoring (IONM) has improved the diagnosis and surgical treatment of brainstem and posterior fossa tumors. Several modalities are available for IONM such as electroencephalography, brainstem mapping (BSM), cranial nerves evoked potentials), somatosensory evoked potentials (SEP), motor evoked potentials (MEP), brainstem auditory evoked potentials (BAEPs), nerve conduction, and electromyography (EMG) signals. Though motor evoked potential (MEP) and brainstem mapping are the most common IONM modalities used for surgical management of brainstem gliomas, cranial nerve potentials can also be of great help. Case description: This article describes a 10-year-old child with diffuse intrinsic pontine glioma (DIPG) who presented with gradual progressive crossed hemiparesis. His brain images carried a range of potential differential diagnoses. Her underwent a successful brainstem biopsy via using motor evoked potential for facial nerve without injuring nearby structures. Conclusion: Motor evoked potential of the facial nerve can be used solely for biopsy taking in cases of DIPG. Highlights: IONM has improved the diagnosis and surgical treatment of brainstem and posterior fossa tumors. MEP and brainstem mapping are the most common IONM modalities used for surgical management of brainstem gliomas, cranial nerve potentials. Motor evoked potential of the facial nerve can be used solely for biopsy taking in cases of diffuse intrinsic pontine glioma (DIPG).